Networks of innovation: towards new models for managing schools and systems (Organisation for Economic Co-operation and Development, 2003)
OECD countries are increasingly referred to as "network societies". This prompts questions about educational networks: to what extent can they replace cumbersome bureaucracies as forms of management and as sources of innovation and professionalism? Some predict the demise of large, slow-changing public services. But what will take their place, and how do we ensure that it will be for the better? As schools become more autonomous and the world more complex, what forms of organization and governance will ensure that education does not fragment into chaos? These are among the questions that inspired seminars held in Hungary, the Netherlands and Portugal, organized with the OECD's Centre for Educational Research and Innovation. They were concerned with the "how?" and not just the "what?" and "why?" of changing schools for the future
This report is the most recent publication of the OECD/CERI project, Schooling for Tomorrow" -- Foreword. - Includes bibliographical references
Keywords: Amtsdruckschrift; Graue Literatur; Konferenzschrift; Bibliografie; Aufsatzsammlung; Schule; Innovation; Bildungspolitik; Ungarn; Portugal; Niederlande; Großbritannien; Innovationsmanagement; Bildungsplanung; OECD